Consideration of USD to BDT exchange rate and request for adjustment of contract price for the unreasonable hike due to the pandemic and war situation - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the response to Tritech about consideration of exchange rate and adjustment of contract price for BRACU new campus project.